Angle-dependent magnetoresistance oscillations and Fermi surface reordering at high magnetic fields in α-(ET)2KHg(SCN)4 - Caulfield, J; Blundell, S; Singleton, J; House, A; du Croo de Jongh, M; Hendriks, P; Perenboom, J; Hayes, W; Kurmoo, M; Day, P (Elsevier, 1995)

(untitled)
Angle dependent magnetoresistance oscillations (AMRO) have been studied in the charge transfer salt α-(ET)2KHg(SCN)4 for magnetic fields in the range 0 - 30 T. This salt exhibits the onset of antiferromagnetic order at temperatures TN approx.8-10 K and the presence below this temperature of a region of sharp negative magnetoresistance at a field around 22 T known as the 'kink'. AMRO have been measured in this salt for a wide range of applied fields since the period, amplitude, and nature of the oscillations can be used to directly infer the character of the Fermi surface (FS) as a function of field. The data indicate that a profound change in the band structure occurs at this kink transition; the high field phase is characterised by quasi-2D oscillations from a closed cylindrical FS which is elongated in the c direction; the low field phase appears to be a spin density wave groundstate, with a FS consisting of a sheet (which is quasi-1D in character and tilted at an angle of approx.21° to the b*c plane) and small closed 2D pockets. It is suggested that the breakdown orbits between the pockets and the 1D sheets are able to account for the various Shubnikov-de Haas frequencies observed below the kink.